Relationship between psychological status and disease activity and quality of life in ankylosing spondylitis - Baysal, Ozlem; Durmus, Bekir; Ersoy, Yuksel; Altay, Zuhal; Senel, Kazim; Nas, Kemal; Ozgocmen, Salih (Springer Heidelberg, 2011)
Our aim in this study was to compare the depression and anxiety risk in patients with AS and healthy controls and also to determine the relationship between disease activity, quality of life and psychological well-being. Two hundred and forty-three patients with ankylosing spondylitis (AS) and 118 age-, sex- and education-matched healthy controls were enroled into the study. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and Functional Index, and Metrology Index, Health Assessment Questionnaire for Spondyloarthropathies (HAQ-S), Hospital Anxiety and Depression Scale (HADS) including depression subscale (HADS-D) and anxiety subscale (HADS-A), Ankylosing Spondylitis Quality of Life (ASQoL) Scale, duration of morning stiffness, pain-visual analogue scale (VAS), patient and physician's global assessment of disease activity (100 mm VAS) were used to assess clinical and psychological status. Patients had similar HADS-D but higher HADS-A than healthy controls. Patients with high risk for depression and anxiety had higher scores in BASDAI, BASFI and also poorer scores in VAS pain, patient global assessment, physician global assessment, HAQ-S and ASQoL. There was a negative correlation of HADS-D and HADS-A scores with educational level of the patients. Higher scores in HADS-D and HADS-A indicated poorer functional outcome and quality of life. Multivariate logistic regression analysis revealed that the HADS-D (OR = 6.84), HAQ-S (OR = 1.76), VAS pain score (OR = 1.03) and ESR (OR = 1.02) were independent risk factors for higher anxiety scores whereas HADS-A (OR = 1.36) and ASQoL (OR = 1.24) were independent risk factors for higher depression scores. The psychological status had close interaction with disease activity and quality of life in patients with AS.
Keywords: Depression; Anxiety; Disease activity; Quality of life; Ankylosing spondylitis